Terrorism a threat to tourism: case study of Kenya - Mhonde, M. (BUSE, 2018)
The research sought to assess the impact of terrorism on the tourism industry in Kenya. The terrorists attacks have increased over past years with adverse effects on tourism industry. Terrorists attacks include the 1975 Nairobi bombing, 1980 Norfolk Hotel attack and also 2015 Garissa University attack. The objectives of the study includes assessing impacts of terrorism on tourism, investigating the reasons why terrorists target tourists centers and examining different strategies used by Kenya to counter terrorism. Constructivism theory was used stating the collective efforts against terrorism. The study adopted a qualitative research methodology and used a population of 32 respondents. Interviews and questionnaires were used to gather information as well as secondary documentary sources. .Expert purposive sampling was used because it sought to identify people whom because of their experiences have special insights into the research question. The study also found out that terrorism in Kenya reduced the number of tourists visiting the country and some hotels and restaurants closed leading to loss of jobs to many people.Terrorists target tourists because of their tourism style which may demonstrate conspicuous consumption. Strategies used to counter terrorism in Kenya include Usalama Watch ,Nyumba Kumi and also partnering with other countries. The study recommends that Kenya should engage in diplomacy with countries that send a large number of tourists and also to invest more on security and security arms equipping them with modern weapons.